The Influence of Work Motivation, Remuneration, and Workload on Employee Performance at PT BPR Sari Wira Tama Badung District - Surya, Ida Ayu Putu Clarantya Dyentari; Sapta, I Ketut Setia; Widyani, Anak Agung Dwi (AIBPM Publisher, 2023)
Human resources are an important asset to an organization because they can determine whether human organizational goals are achieved. The purpose of this study is to determine the impact of work motivation, compensation and workload on employee performance. This research was conducted at PT. BPR Sari Wira Tama Badung Regency, The research object in this study is work motivation, remuneration, workload on employee performance. The population and sample in this study were all employees at PT. BPR Sari Wira Tama, Badung Regency, totaling 41 employees. The sampling technique used was the saturated sampling method so that all employees were used as research respondents. The data analysis technique used in this study was multiple linear regression analysis processed using SPSS version 26 software. Based on the analysis results, this study shows that work motivation has a positive and significant impact on PT employee performance. The number of BPR Sari Wira Tama Badung Regency will be increased. Compensation has a positive and significant impact on employee performance in PT. The number of BPR Sari Wira Tama Badung Regency will be increased. Workload has a significant negative impact on PT staff performance. BPR Sari Wira Tama Badung Regency will experience a recession.